Implementasi Pola Asuh Pondok Pesantren Darul Hikmah Menganti dalam Internalisasi Nilai-Nilai Religius Santri Usia Dasar - Danella Ayu Febriana Putri; Taufiqurrahman Taufiqurrahman (Fakultas Tarbiyah dan Kegurusn Universitas Islam Bandung, 2026)
This study analyzes the implementation of parenting patterns at Darul Hikmah Menganti Islamic Boarding School in internalizing religious values among elementary-aged students. Using a qualitative field research approach, data were collected through observation, interviews, and documentation involving caregivers, administrators, and 5th–6th grade students over three months. Findings indicate that the boarding school applies a democratic parenting pattern implemented holistically through 24-hour mentoring across six life dimensions: spiritual, physical, emotional, social, academic, and expressive. Religious value internalization occurs simultaneously through three interconnected stages-transformation, transaction, and transinternalization embedded in every daily activity. The dynamic balance between structured control and emotional warmth facilitates authentic value internalization in elementary-aged students.